Studies on the deterioration of retail tiger prawns (Penaeus monodon) in Philippine wet markets - Masinag, Silahis B.
The general objective of this study is to monitor the deterioration of tiger prawns (Penaeus monodon) I involved the enumeration of the procedures and techniques used in handling conditions during retail were also noted. The second phase involved the sampling of retail tiger prawns at specified schedules during the duration of the display in wet markets. Quality assessment of the samples was then conducted to determine the rate of deterioration during the display sale of the tiger prawns. Analyses which were conducted included physico-chemical and microbiological examinations. Throughout the 12 h of display of the tiger prawns, the holding temperatures of iced tiger prawns were found to be between 12°-19°C, and reached the maximum temperature during the midday. The prawn samples, during the entire duration of the display, were described as whole without being split or broken and had no signs of discoloration such as black spots. Flavor and odor of the samples showed the absence of H₂S, ammonia, trimethyl amine, or other objectionable odor. The tissue and texture was described as firm and elastic, and without signs of any spongelike tissue. Total plate counts of the samples increased from n initial average counts of 1.75 x 10⁶ cfu/g after 12 h of display. Coliform counts also increased from >560 MPN/g to >1100 MPN/g for the same duration of the display. An increase in the pH of the prawn muscle was observed from pH 6.3- 6.4 after 3 h of storage. On the 6th h, the pH again decreased to pH 5.9 until the 12th h of display. Trimethyl amine (TMA) levels ≥1 was not detected on all prawns samples obtained all throughout the 12 h of display. Initial TVN values of 3.41 mg/100g increased during the first 3 hours of display to TVN levels of 5.99mg/100g. This was followed by a decrease to 3.67mg/100g on the 6th h before finally increasing again to 5.77 and 13.65mg/100g for the 9th and 12th h respectively. The κ- value of the retail tiger prawns continuously increased during the duration of the display from an initial value of 12.31% to values of 56.09% for the 12th h of display. Softening the prawn meat was observed after 3 h of storage as shown by the increase in the penetrometer readings form an initial of 121 1/10THmm to 141 1/10THmm. It was then followed by a decrease to 134 1/10THmm on the 6th h which indicated a slight toughening. Further display of the prawns resulted in the eventual softening of the prawns muscle on the 9th and 12 h with penetrometer readings of 143 and 151 1/10THmm, respectively.